A Systematic Review of Entrepreneurial Family: Perspectives and Theoretical - JAMIL, MAHWISH; FADZIL, AHMAD FIRDAUSE MD; WAQAR, AMBER; YAACOB, MOHD RAFI (The journal of contemporary issues in business and government, 2021)
The research on entrepreneurial family business is increasing from the last decades with different perspectives. The entrepreneurial family researches contributed different ways of conceptualizing the entrepreneurial family business based on highly complex literature reviews. Still, this field is emerging, and potential for further research to fill the gaps in different areas. The current research presented a systematic review based on the period of 2010 to 2020 for understanding family business content and theoretical perspective comprehensively. The study findings highlighted how entrepreneurial family business pursues through different conceptualization and theoretical perspectives. A plethora of study is found on family businesses worldwide based on organizational performance, business ownership, corporate governance, business succession and organizational culture. However, few studies corroborated theories to explain the entrepreneurial family business phenomenon. The theories discussed in this review are resource based view theory, agency theory, stewardship theory, multi and meso level theory and sociological theory for describing the entrepreneurial family business. Moreover, the future direction is also given in this study to fill the potential in this field.